The Influence of Soft Skills, Hard Skills, and Self-Efficacy on Entrepreneurial Interest with Entrepreneurship Education as a Mediating Variable in Management Students of the Class of 2022 Faculty of Business Economics - Baiq Nursahdian; Djoko Suprayetno (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
This study examines the influence of soft skills, hard skills, and self-efficacy on entrepreneurial interest with entrepreneurship education as a mediating variable in Management students of the 2022 FEB UNRAM class, amidst the low level of entrepreneurship in Indonesia (BPS, 2024). The aim is to test the causal relationship through an explanatory quantitative approach with SEM-PLS. The population was 58 students, using saturated sampling. The Likert scale questionnaire instrument was validated through loading factor >0.70, Cronbach's Alpha >0.70, and analyzed via SmartPLS with bootstrapping. The results show that hard skills and self-efficacy have a significant direct positive effect on entrepreneurial interest (coefficients 0.453 and 0.3, p<0.05), while soft skills do not (p=0.079); all three influence entrepreneurship education, which mediates the indirect relationship (p<0.01). In conclusion, entrepreneurship education strengthens skills and self-confidence to increase entrepreneurial interest, suggesting integration of practical curriculum.